2010
DOI: 10.1111/j.1467-7687.2010.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of anger and inhibitory control in twins from 12 to 36 months of age

Abstract: Inhibitory control (IC) is a dimension of child temperament that involves the self-regulation of behavioral responses under some form of instruction or expectation. Although IC is posited to appear in toddlerhood, the voluntary control of emotions such as anger begins earlier. Little research has analyzed relations between emotional development in infancy and later emerging IC. We examined phenotypic associations and genetic and environmental influences on parent-and laboratory-assessed anger and IC in a twin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 61 publications
11
84
2
3
Order By: Relevance
“…Our Lab-TAB temperament composites showed low to moderate intercorrelations, a finding that was expected based on our prior studies (Gagne, Saudino & Asherson, 2011; Gagne & Goldsmith, 2011; Pfeifer, Goldsmith, Davidson, & Rickman, 2002). Also expected, associations across dimensions were much stronger within and between mother and father ratings.…”
Section: Discussionsupporting
confidence: 87%
“…Our Lab-TAB temperament composites showed low to moderate intercorrelations, a finding that was expected based on our prior studies (Gagne, Saudino & Asherson, 2011; Gagne & Goldsmith, 2011; Pfeifer, Goldsmith, Davidson, & Rickman, 2002). Also expected, associations across dimensions were much stronger within and between mother and father ratings.…”
Section: Discussionsupporting
confidence: 87%
“…First, our finding that parent ratings of IC show higher age-to-age stability than observer ratings is common in the literature (Saudino, 2003). In fact, the GEO study found a similar pattern of high stability for parent ratings and no stability for Lab-TAB ratings of anger across 12 and 36 months (Gagne & Goldsmith, 2011). Although it is possible that the higher stability for parent ratings is due to stability in the parent’s rating behaviors or their expectancies, this is unlikely given that it is genetic factors that largely explain the phenotypic age-to-age correlation for IC in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Only two of these studies have examined early IC in the context of a multi-method approach employing parent ratings and lab-based assessments (e.g., Gagne & Goldsmith, 2011; Gagne & Saudino, 2010). Both used Lab-TAB IC episodes as behavioral assessments, and standard parent rating questionnaires in moderately-sized twin samples.…”
Section: Introductionmentioning
confidence: 99%
“…Further, non-normative temper loss predicts the onset of mood and behavioral symptoms and disorders 16 months later [85]. In infants, it is possible to identify individual differences in responses to frustration; maternal, rather than lab-based, measures, are better predictors of irritability in toddlerhood [86, 87]. A new wave of lab-based and observational studies in infants using novel techniques may have more predictive power.…”
Section: Irritability In Childrenmentioning
confidence: 99%